29 Long-term outcomes in the surgical management of left ventricular outflow tract obstruction in hypertrophic cardiomyopathy. (28th September 2016) - Collis, R; Watkinson, O; O'Mahony, C; Guttmann, O; Elliott, P
Abstract : Hypertrophic Cardiomyopathy is the most common genetically inherited cardiac disease affecting 1 in 500 of the population. Dynamic Left Ventricular Outflow Tract Obstruction (LVOTO) caused by systolic anterior motion of the mitral valve is present in up to two thirds of patients. Surgical intervention can alleviate LVOTO and improve symptoms but the risks and long-term outcomes of different surgical strategies are unknown. Methods: Survival and clinical outcomes were assessed at 1, 5 and 10 years post operatively in 362 patients with HCM undergoing surgical intervention for LVOTO at a specialist cardiomyopathy centre. The primary survival endpoint was all cause mortality. Results: Group A (n = 286) underwent septal myectomy; Group B (n = 32) underwent septal myectomy and MV repair; Group C (n = 26) underwent myectomy and MV replacement and Group D (n = 17) underwent MV replacement without myectomy. There were 93 concomitant procedures including CABG, AVR, MAZE procedure and left atrial appendage closure across groups. Mean follow up was 6.2 years and longest follow up was 46.6 years. NYHA functional class improved from 2.49 to 1.48 postoperatively (p < 0.05). The mean resting LVOT gradient improved from 72 mmHg to 13.6 mmHg at 1 year post procedure; 14.4% of patients were operated on because of latent obstruction. There were 16 repeat surgeries including 9 redo myectomies, 6 MV Replacements and 1 MV Repair with a mean time to reintervention of 5.3 years. 28 patients met the primary endpoint of all-cause mortality at a mean of 9.6 years. There were 4 procedural related mortalities and 24 mortalities on late follow up greater than 30 days post procedure. Survival analysis was estimated using Kaplan-Meier curves and log-rank testing. Estimated survival rates post-operatively at 1, 5 and 10 years respectively were 98.9%, 97.5%, 93.7% in group A; 97%, 97%, 32.3% in group B 96.2%, 90.5%, 90.5% in group C; and 93.3%, 80%, 80% in the group D (p < 0.05). Conclusion: Different surgical techniques are adopted for the management of LVOTO. Septal myectomy in particular is shown to have good long term outcomes with low rates of reintervention.